0598 Nocturnal SOREMPs As A Predictor Of The Severity Of Narcolepsy In Asian Polulation. (12th April 2019) - Hong, Seung-Chul
Abstract: Introduction: The aim of this study is to investigate the diagnostic characteristic of the narcoleptic groups, which are categorized based on the presence of nocturnal sleep onset rapid eye movement sleep period (nSOREMP). Methods: Subjects included 167 narcoleptic patients diagnosed at the St. Vincent Hospital, the Catholic University of Korea. They underwent polysomnography and Multiple Sleep Latency Test for objective sleep parameter. The standardized face to face interview and Epworth Sleepiness Scale (ESS) was used to inquire about daytime functioning of patients. Overall retrospective chart review was performed on their sleep health data. Results: Subjects without nSOREMP demonstrated a higher percentage of stage 1 sleep and more frequent arousals. This signified that they were having a lower quality of sleep compared to the subjects without nSOREMP. In terms of daytime functioning, they showed lower ESS score (P=0.05) in the group without cataplexy. Conclusion: The presence of nSOREMP and cataplexy demonstrates worse daytime functioning and lower quality of sleep at night. Our study thereby suggests that nSOREMP possibly be the predictor of the symptoms and prognosis of narcolepsy patients. Support (If Any): There is nothing to be declared.